Seasonal Variation in the Home Ranges of Black Curassow, Crax alector, in French Guiana. (November 2021) - Lormée, Hervé; Berzins, Rachel; Rocheteau, Vincent; Coster, Fran De; Denis, Thomas; Richard-Hansen, Cécile
Cracidae is the most threatened avian family in the Neotropics, mainly because of habitat destruction, heavy hunting pressure and poaching. In French Guiana, Black Curassows are heavily hunted, although basic knowledge of the ecological and demographical traits of the species remains limited. Such a gap prevents any attempt to assess the impact of hunting and to help stakeholders to develop proposals ensuring hunting sustainability. The spatial relationship between animals and their habitat is important for conservation management, being related to population densities through complex patterns. Here, we report on a radio-tracking study of Black Curassows in tropical primary rainforest, in Nouragues National Reserve, French Guiana. The aims of the study were to estimate home range size and its variation across seasons, and to quantify movement patterns of the birds. We captured and fitted VHF tags to four adults, and tracked them for 10 to 21.5 months. Daily movements were recorded, and home ranges estimated using the Kernel Density method, for two consecutive wet seasons and one dry season. Using 95% and 50% Kernel densities, the average annual home range and core area were 96.3± 32.6 ha (SE) and 22.8 ± 2.8 ha respectively. Home ranges appeared spatially stable over the two years, and overlapped between neighbouring groups. During the dry season, Black Curassows did not migrate but tended to enlarge their home range, with greater daily movements and higher home range overlap. Although additional data are still needed, our results can help to improve the knowledge and management of this poorly studied species.